Alat Kendali Lampu Rumah Menggunakan Bluetooth Berbasis Android - Andri Saputra; Dwi Febriansyah; Haris Kuswara (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2014)
The tools used by humans is currently expected to have more value in relieving human work, the more it value, among others, is the ability of the tool to better facilitate people doing an activity. For example to control home lights have to do with the switch, it at least can be changed by merging some of the technology that is currently growing, especially for the growing number of smartphone users to use, by means of the control lights using bluetooth android-based home can overcome these problems so that they can control the light house with easy, efficient, practical in use, and can improve the comfort in controlling home lighting without the need to interact directly with the power switch.